Indicateurs de mesure de la pression anthropique sur les ressources naturelles : exemple de la périphérie du Parc « W » dans la commune rurale de Tamou au Niger - Mahamadou Sani Moussa; Boureima Amadou (VertigO, 2014)
This paper describes the experience of a university research project in line with the work on the management of natural resources, landscape dynamics and ecosystem of peripheral rural areas in the protected area of W of Niger. Through the mode of agricultural production in the local villagers Senokonkédjé and pastoral system Tulwarey both in the rural town of Tamou, the study aims to characterize the environment, to point out the physical indicators , ecological and social indicators that highlight evidence the evolution and transformation of the environment. Its indicators are both qualitative and quantitative ; these indicators are used as means of measuring and assessing the state of human pressures on RTFT and National Park W. Human occupation of the immigration process, the gradual progress of cultivation areas, overgrazing places, recurrent droughts and pernicious use of natural resources give the extent of the changes that have occurred and announce the warning signs threats on RTFT and sanctuary area of the reserve of W. The methodological approach is based on an inclusive and iterative process with stakeholders operating at the periphery of the reserve in both villages and the area of Tamou. It focuses on the observation of human practices through the agropastoral system, reading and perception of people around the recent evolution of the landscape in the area over the past 40 years. It is complemented by the analysis of statistical data and thematic maps produced as part of the project. The results show an increase of anthropogenic activities that stretch towards the subject that once never knew this space, the remarkable transformation of the landscape on the physical and biological. They are expressed in the form of indicators to assess the current state of pressure on the reserve and its immediate surroundings and are able to assist in decision making for the sustainable management of natural resources in this specific area.